Angiotensin II, progesterone, and prostaglandins are sequential steps in the pathway to bovine oocyte nuclear maturation - Siqueira, Lucas Carvalho; Barreta, Marcos Henrique; Gasperin, Bernardo; Bohrer, Rodrigo; Santos, Joabel Tonellotto; Buratini Junior, Jose [UNESP]; Oliveira, Joao Francisco; Goncalves, Paulo Bayard (Elsevier B.V., 2012)
Oocyte meiotic resumption is triggered by the ovulatory gonadotropin surge; in cattle, angiotensin II (AngII) and prostaglandins (PG) are key mediators of this gonadotropin-induced event. Here, we tested the hypothesis that progesterone (P-4) is also involved in oocyte meiotic resumption induced by the gonadotropin surge. In Experiment I, P-4 induced nuclear maturation in a dose-dependent manner using a coculture of follicular hemisections and cumulus-oocyte complexes. In the second experiment, using an in vivo model, an injection of mifepristone (MIFE; P-4 receptor antagonist) at the antrum of preovulatory follicles prevented GnRH-induced oocyte meiotic resumption in vivo. In Experiment III (coculture system similar to that of Experiment I), MIFE prevented stimulatory effects of AngII on resumption of meiosis, but saralasin (AngII receptor antagonist) did not inhibit P-4 actions. In Experiments IV and V, fibroblast growth Factor 10 (FGF10; known to suppress steroidogenesis in granulosa cells), blocked AngII-but not P-4-induced oocyte meiotic resumption. Therefore, we inferred that AngII is upstream to P-4 in a cascade to induce meiotic resumption. Previously, we had reported that AngII acted throughout the PGs pathway to modulate nuclear progression. In Experiment V, indomethacin inhibited resumption of meiosis induced by P-4, providing further support to the AngII-P-4, sequential effect on meiotic resumption. In conclusion, we inferred that AngII, P-4, and PGs are sequential steps in the same pathway that culminates with bovine oocyte maturation. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ovulation; Meiotic resumption; Angiotensin; Steroid; Eicosanoid